2017
DOI: 10.3904/kjim.2016.092
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic role of mean platelet volume and neutrophil to lymphocyte ratio in childhood brucellosis

Abstract: Background/AimsBrucellosis patients present various non-specific clinical symptoms, such as fever, fatigue, sweating, joint pain, arthritis, myalgia, and headache. Based on the nonspecifity of its clinical signs and symtoms, we decided to evaluate whether mean platelet volume (MPV) , neutrophil to lymphocyte ratio (NLR), and platelet to lymphocyte ratio (PLR) will contribute to the diagnosis.MethodsIn this retrospective study, we reviewed hospital-records of 60 children with a confirmed diagnosis of brucellosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 24 publications
0
34
2
1
Order By: Relevance
“…Research results show that hematological parameters in patients with brucellosis differ from patient to patient and these parameters can return to their normal value after the treatment of brucellosis. 6 The inflammatory process that occurs during brucellosis is associated with an increase in acute-phase reactants. 18 CRP is an acute-phase protein that increases up to 1000fold in the blood of patients with infection or inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Research results show that hematological parameters in patients with brucellosis differ from patient to patient and these parameters can return to their normal value after the treatment of brucellosis. 6 The inflammatory process that occurs during brucellosis is associated with an increase in acute-phase reactants. 18 CRP is an acute-phase protein that increases up to 1000fold in the blood of patients with infection or inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…22 Another study reported that patients with the acute brucellosis exhibited higher CRP levels than the control group. 6,13,23 Some other studies have suggested that elevated CRP level may also be associated with disease severity and mortality in hospitalized patients with community-acquired pneumonia. 24 In our study, CRP was significantly higher in brucellosis patients, which indicates that CRP is a valuable marker for the diagnosis of brucellosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations